Toxicity of aluminium to black pepper (piper nigrum L.) in Sarawak - De Waard, P.W.F.; Sutton, C.D. (Nature Publishing Group, 1960)
SYMPTOMS of an unknown disorder have been increasingly observed on pepper vines since 1956 ; no pathogen seemed to be involved. Affected vines show an overall bright green to yellow colour and their leaves a pronounced droop. Individual leaves first show symptoms of a speckled necrosis mostly along the main veins, each brown spot having a surrounding yellow halo. Afterwards the necrotic areas spread and become more serious so that finally the leaves fall. These vines have a greatly reduced root system, which dies off centripetally. Different stages of the leaf symptoms are shown in Fig. 1.